Status, Challenges and Directions of Research Involvement of Teachers: A Baseline Study for Research and Development Intervention Program in Dinagat Division - Paymalan, Irmalyn; Elben Joy B. Erno, (IJRDO- Journal of Educational Research, 2020)
DepEd through DepEd Order No. 65, s. 2003mandates the institutionalization of the research-based decision and policy making in the department. Nevertheless, in remote areas like Dinagat Islands, only few teachers, both in public and private schools, were involved in research. As baseline study for the research and development intervention program of Dinagat Division, this study aimed to find out the status, challenges and directions of research involvement of private and public school teachers in the Division of Dinagat Islands. Specifically, the study sought data on the profile of the private and public school teachers in terms of age, sex, educational attainment, length of service, and research output; the issues and challenges encountered in conducting research by private and public school teachers in the schools division of Dinagat Islands in terms of knowledge about research, financial aspect, time allotment, other motivational factors such as self-advancement, family support, and proximity/distance/accessibility; the directions of the school that would help improve research involvement of private and public school teachers as to plan of action, and technical assistance; and the significant effect of the profile of the teachers to the challenges they encountered in conducting research. The study also design a classification model discriminating the research status of the teachers as to be able to complete or not. The results of this study served as basis for a research program that would address the issues and challenges of research involvement of private and public school teachers of Dinagat Islands.The explanatory sequential design was employed and only 51 were considered as respondents of the study. The instruments used were researcher made questionnaire and a semi structured interview for teachers and school heads to suit the assessment needs of the paper. Gathered data were treated using Frequency Count and Mean, Univariate ANOVA and Discriminant Analysis. In the qualitative analysis, the researcher transcribed, coded, and analyzed the interview part for common themes.The findings revealed that both private and public school teachers encountered challenges in conducting research such as knowledge on research and financial support. In terms of school direction, motivating and mentoring/coaching are the technical assistance given to them. On the other hand, skills development, research partnerships, and rewarding are planned strategy of the school to improve the research involvement of private and public school teachers. The teachers in the public schools encountered greater challenges on time allotment in conducting research, compared to the teachers in the private schools. The teachers’ educational attainment is accounted for the expected variation of challenges they encountered on time allotment and the motivating factor family support. The knowledge and mastery of the technicalities in conducting research plays the most important contribution on discriminating the status of research of the schools in Dinagat Islands whether redssearch can be completed or not. The classification model of the status of research of the teachers based on the challenges they met in conducting researches with 76.5% accuracy is given by the functionStatus score = -0.851 Knowledge + 0.382 Financial Aspect + 0.154 Time Allotment + 0.095 Self-advancement + 0.019 Family support + 0.208 Proximity/Distance/Accessibility, where the status is classified as not completed when score is below -0.104 and identified to be able to complete when the score is above it.